Pemanfaatan Kulit Pisang Kepok (Musa paradisiaca ) dalam Pembuatan Bolu Kukus - Aprilia Indah Pangestika; Mia Srimiati (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2020)
This study aims to determine the substitution effect of banana peel flour based on the proximate tests (water content, ash, carbohydrate, protein, fat and fiber). This experimental study used Completely Randomized Design (CRD) to find out the best quality of banana skin flour with the substitution level of kepok banana peel as a treatment. There were 4 treatments, F1 (45%), F2 (50%), F3 (55%) and F0 (without kepok banana peel flour). Based on the results of statistical tests using Analysis of Variance (ANOVA and Duncan’s Multiple Range Test, substitution of kepok banana peel flour has a significant effect (p 0.05) on the organoleptic properties. Steamed sponge cake substituted with 50% kepok banana peel flour (F2) was the formula with the highest acceptability compared to other formulas. Formula F2 (50%) showed the water content of 31,60%, ash level 2,78%, fat 5,97%, protein 10,97%, fiber 1,91%, and carbohydrate 48,68%. Kepok banana peel flour can be used as an alternative to diversification of food and increase the nutritional value of steamed sponge cake. Penelitian ini bertujuan untuk mengetahui pengaruh substitusi tepung kulit pisang kepok berdasarkan uji proksimat (kadar air, abu, karbohidrat, protein, lemak dan serat). Penelitian ini merupakan penelitian eksperimental menggunakan Rancangan Acak Lengkap (RAL) untuk mengetahui kualitas tepung kulit pisang terbaik dengan tingkat subsitusi tepung kulit pisang kepok sebagai perlakuan, yaitu F1 (45%), F2 (50%), F3 (55%) dan F0 (tanpa tepung kulit pisang kepok). Berdasarkan hasil uji statistik menggunakan Analysis of Variance (ANOVA) dan Duncan’s Multiple Range Test, substitusi tepung kulit pisang kepok berpengaruh signifikan (P0,05) terhadap hasil organoleptik produk. Bolu kukus yang disubstitusi tepung kulit pisang kepok sebanyak 50% (F2) merupakan formula dengan daya terima paling tinggi dibandingkan dengan formula lain. Formula F2 (50%) memiliki kadar air 31,60%, abu 2,78%, lemak 5,97%, protein 10,97%, serat 1,91%, karbohidrat 48,68%. Tepung kulit pisang kepok dapat dijadikan alternatif sebagai diversifikasi pangan dan meningkatkan nilai gizi pada bolu kukus.